Real Earnings Management in Family-Affiliated Firms: Empirical Evidence from Malaysia - Wan Abdul Rahman, Wan Nadiah; Mansor, Noorhayati (Asian Journal of Accounting Perspectives, 2019)
Research aim: This paper examines the effects of size and complex structure of family-affiliated business groups on Real Earnings Management (REM) practices in Malaysian listed firms. Design/Methodology/Approach: Family-affiliated business groups listed on Bursa Malaysia during the years 2006 to 2015 filtered using specific criteria were selected as the sample. STATA software was used to analyse the panel data, and two different regression models were run for the empirical testing to examine the effects of size and group complexity. Research finding: It is evidenced that the size and complexity structure of family-affiliated business groups are positively associated with REM, measured by abnormal cash flow from operations and abnormal discretionary expenses, but negatively associated with abnormal production cost. Theoretical contribution/Originality: Since previous studies based on Malaysian public listed firms focus on Accruals Earnings Manipulation (AEM), this study broadens the scope by providing empirical evidence on the relationship between family-affiliated firms’ characteristics and REM. Practitioner/ Policy implication: Investors, auditors, analysts and practitioners should consider family-affiliated firms as a factor that significantly induces earnings manipulation. The result is also relevant for regulators in regulating takeover rules or tax policy to affiliated groups in order to create incentives for them to maintain a specific size or complexity structure, or otherwise, be penalised for exceeding the size or complexity characteristics. Research limitation/ Implication: The results from this study may apply to Asian countries with similarities in family ownership to that in Malaysia. The findings, however, may not apply to developed countries where family concentration and pyramidal structure are not significant. Keywords: Real Earnings Management, Family-Affiliated Firms, Emerging Market, Entrenchment Effect, Malaysia Type of article: Research paper JEL Classification: M41